Recruitment Dynamics of Age‐0 Yellow Perch in a Drowned River Mouth Lake: Assessing Synchrony with Nearshore Lake Michigan. Issue 2 (19th February 2013) - Janetski, David J.; Ruetz, Carl R.; Bhagat, Yakuta; Clapp, David F.
Abstract: We assessed recruitment dynamics of juvenile Yellow Perch Perca flavescens in coastal habitats of eastern Lake Michigan. To investigate recruitment patterns and associations with environmental factors in a coastal drowned river mouth (DRM) lake, we sampled juvenile Yellow Perch seasonally in Muskegon Lake, Michigan, during 2003–2011. We also sampled three nearshore sites in Lake Michigan each fall to evaluate synchrony between the DRM lake and nearshore habitat. In Muskegon Lake, age‐0 Yellow Perch CPUE during fall was high in 2005 and 2007; moderate in 2008, 2010, and 2011; and low in other years. Fall CPUE (age 0) was positively associated with CPUE in the next spring (age 1; slope = 0.98; R 2 = 0.95), which we attribute to high overwinter survival. Fall CPUE of age‐0 Yellow Perch showed a positive relationship with June air temperature ( R 2 = 0.76), suggesting that warm conditions at early larval stages positively influence recruitment of juveniles. Juvenile recruitment in Muskegon Lake was not synchronized with juvenile recruitment in nearshore Lake Michigan. The lack of synchrony may be an indication that (1) age‐0 Yellow Perch recruitment in DRM lakes and Lake Michigan are influenced by different environmental controls and (2) dispersal between the two habitats does not strongly affect age‐0 recruitment dynamics.